Primary bone lymphoma of the distal femur – a case report - Basu, Praloy (International Journal of Research in Orthopaedics, 2025)
Primary bone lymphoma (PBL) is a rare extranodal lymphoma that arises within skeletal structures, most often as diffuse large B-cell lymphoma (DLBCL). It typically presents with localized pain and swelling and requires a high index of suspicion for diagnosis. A 53-year-old man presented with pain and swelling over the distal femur. Imaging revealed a lytic-sclerotic lesion with cortical breach and soft-tissue extension. Biopsy confirmed large B-cell lymphoma, germinal center subtype. Staging workup showed no nodal or marrow involvement, consistent with Stage IE disease. The patient was treated with one cycle of CVP followed by six cycles of Rituximab, Cyclophosphamide, Hydroxydaunorubicin, Oncovin and Prednisone (R-CHOP) and involved-field radiotherapy (40 Gy/20 fractions). Post-treatment positron emission tomography-computed tomography (PET-CT) showed complete metabolic response. Combined-modality treatment with R-CHOP chemoimmunotherapy and radiotherapy offers excellent outcomes in localized PBL. Early diagnosis, accurate staging, and multidisciplinary management are crucial for durable remission and optimal survival.